Degradation of creatinine using boron-doped diamond electrode: Statistical modeling and degradation mechanism. (September 2017) - Zhang, Zhefeng; Xian, Jiahui; Zhang, Chunyong; Fu, Degang
Abstract: This study investigated the degradation performance and mechanism of creatinine (a urine metabolite) with boron-doped diamond (BDD) anodes. Experiments were performed using a synthetic creatinine solution containing two supporting electrolytes (NaCl and Na2 SO4 ). A three-level central composite design was adopted to optimize the degradation process, a mathematical model was thus constructed and used to explore the optimum operating conditions. A maximum mineralization percentage of 80% following with full creatinine removal had been achieved within 120 min of electrolysis, confirming the strong oxidation capability of BDD anodes. Moreover, the results obtained suggested that supporting electrolyte concentration should be listed as one of the most important parameters in BDD technology. Lastly, based on the results from quantum chemistry calculations and LC/MS analyses, two different reaction pathways which governed the electrocatalytic oxidation of creatinine irrespective of the supporting electrolytes were identified. Highlights: Boron-doped diamond was initially used to degrade creatinine. The mineralization was favored in case of low chloride concentration. Supporting electrolyte concentration was a crucial parameter for BDD technology. Quantum chemistry calculation and LC/MS were used for mechanistic study. Creatinine degradation pathways in both electrolyte medium were proposed.